2014
DOI: 10.4321/s1886-36552014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Apps: a new frontier on the digital landscape?

Abstract: *Background: Over the course of recent years smartphone and tablet technology has evolved rapidly. Similarly, the sphere of healthcare is constantly developing and striving to embrace the newest forms of technology in order to optimise function. Many opportunities for mobile applications (i.e. 'apps') pertinent to the healthcare sector are now emerging. Objective: This study will consider whether registered pharmacists within the United Kingdom (UK) believe it appropriate to use mobile apps during the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In our study, 55.00% of the students were using mobile health apps to monitor or change personal health behaviour whereas 97.00% of the students were using medical apps in another study [25]. Mobile health apps safe and useful in pharmacy practice according to the study conducted in the UK [26]. Similarly, in our study, it was demonstrated that almost all of the pharmacy students agreed that the medical apps were important tools to use in pharmacy practice.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, 55.00% of the students were using mobile health apps to monitor or change personal health behaviour whereas 97.00% of the students were using medical apps in another study [25]. Mobile health apps safe and useful in pharmacy practice according to the study conducted in the UK [26]. Similarly, in our study, it was demonstrated that almost all of the pharmacy students agreed that the medical apps were important tools to use in pharmacy practice.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, pharmacology apps targeting clinicians, pharmacists, and other HCPs provided references for dosing, interactions, and alternative drugs. The incorporation of pharmacology apps into HCPs’ daily practice appears to be a mainstay in China and many other countries [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Mobile apps have infiltrated into society through services including gaming, social networking, news, education and healthcare. As previously reported 3 , the rapid evolution of software platforms on advanced mobile devices over the past decade has paved the way for mobile healthcare (mHealth) apps, which have seamlessly infiltrated healthcare systems in the developed world. 1 At present, thousands of mHealth apps are available 4 , 5 and include for example ‘Dario’ and ‘MyMeds’.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the pharmacist is able to conduct medicines use reviews (MURs) and deliver the new medicines service (NMS) in order to underscore the importance / use of prescribed medication and why it is imperative to take medication as prescribed. 3 Notwithstanding the success of such advanced services, scope now exists to exploit mobile technology platforms along with app-based software to support the patient in following daily treatment plans to optimise treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation